Pemphigus Oral Lesions Intensity Score (POLIS): A Novel Scoring System for Assessment of Severity of Oral Lesions in Pemphigus Vulgaris - Sindhuja, Tekumalla; De, Dipankar; Handa, Sanjeev; Goel, Sonu; Mahajan, Rahul; Kishore, Kamal (Frontiers in Medicine, 2020)
Background: Many patients with Pemphigus Vulgaris (PV) in India present with predominant/ exclusive oral mucosal lesions. Current validated scoring systems for pemphigus do not adequately represent the clinical variability of oral lesions. Objective: To develop and validate a novel scoring system exclusively for oral lesions in PV. Methods:  In this cross-sectional study, the Delphi method was used to build an initial scale that was administered in 115 patients with PV. Exploratory factor analysis was used to examine the underlying factor structure of the new scale. The psychometric properties of the new scale were studied. Correlations between the new scale and Autoimmune Bullous Skin Disorder Intensity Score (ABSIS), Pemphigus Disease Area Index (PDAI) and Physician Global Assessment (PGA) were also assessed. Results: Content validity of the initial scale was established with an average content validity index (CVI) of 0.8. Exploratory factor analysis resulted in a 3-factor structure with a total of 9 items. Corrected item-total correlations, a measure of data quality, was more than 0.30 for all items in the new oral mucosal scale- Pemphigus Oral Lesions Intensity Score (POLIS). Significant correlations were observed between POLIS and oral ABSIS (r= 0.85, p< 0.001), mucosal PDAI (r= 0.70, p< 0.001) and PGA (r= 0.60, p< 0.001). POLIS was also reliable with good internal consistency (Cronbach α= 0.86) and strong inter-rater agreement. Limitations: The study cohort included participants from a single center. Usability and time taken to administer the scale were not assessed. Conclusions: The new scale- POLIS has adequate validity and reliability. It includes both quality of life and clinical disease severity parameters, assessing disease severity holistically. Further studies evaluating the scale’s responsiveness to change are in progress.